Command Secondary School Teachers’ Intention to Use electronic Media for Teaching in Lagos State - Olumorin, Charles Olubode; Onojah, Amos Ochayi; Bello, Ibrahim Shaibu; Onojah, Adenike Aderogba (Indonesian Journal of Curriculum and Educational Technology Studies, 2021)
This study investigated teachers’ intention to use electronic media; and teachers’ intention to use electronic media based on gender, experience and qualification. The study was a descriptive type, 280 randomly selected teachers adequately responded to the questionnaire. Mean scores and t-test were used to for the data analysis. The study revealed that teachers had positive intention to use electronic media. There was significant difference between male and female teachers’ intention to use electronic media for teaching with p=0.02; and There was no significant difference between qualified and less qualified as well experienced and less-experienced teachers’ intention to use electronic media for teaching. The study concluded that the society has embraced electronic devices and relies much on it for socio economic pursuit, The study thus recommended that directorate of command secondary schools should imbibe the use of motivational strategies for staff in the application of electronic media in the teaching. Abstrak Penelitian ini menelisik kecenderungan guru dalam menggunakan media elektronik; termasuk dilihat dari jenis kelamin, pengalaman dan kualifikasi mereka. Penelitian ini merupakan penelitian deskriptif, 280 guru yang dipilih secara acak untuk mengisi kuesioner. Nilai rata-rata dan uji-t digunakan untuk analisis data. Hasil penelitian ini mengungkapkan bahwa guru memiliki kecenderungan positif untuk menggunakan media elektronik. Ada perbedaan yang signifikan antara niat guru laki-laki dan perempuan untuk menggunakan media elektronik untuk mengajar dengan p=0,02. Di sisi lain, tidak ada perbedaan yang signifikan antara kecenderungan guru yang berkualitas dan kurang berpengalaman serta kurang berpengalaman dalam menggunakan media elektronik untuk mengajar. Penelitian ini menyimpulkan bahwa masyarakat pada dasarnya telah familier dan sangat menggantungkan aktivitasnya dengan perangkat elektronik untuk keperluan ekonomi. Oleh karena itu, penelitian ini merekomendasikan bahwa direktorat komando sekolah menengah harus mengakomodasi penggunaan strategi motivasi bagi staf dalam penerapan media elektronik dalam pengajaran.